Additive and generalized additive models: A survey - Michael G. Schimek; Berwin A. Turlach (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
This paper is the attempt to summarize the state of art in additive and generalized additive models (GAM). The emphasis is on approaches and numerical procedures which have emerged since the monograph of Hastie and Tibshirani (1990) although reconsidering certain aspects of their work. Apart from GAM, vector GAM (VGAM), alternating conditional expectations (ACE), and additivity and variance stabilization (AVAS) are discussed. Last but not least there are software hints for all these models.
urn:nbn:de:kobv:11-10060680
Keywords: 330